Efficacy, Radiological Response and Local Toxicity in Locally Advanced Head and Neck Squamous Cell Carcinoma Patients (LAHNSCC) Treated with Hypofractionated Accelerated IMRT with Concomitant Simultaneous Integrated Boost (SIB) - Naveen, Thimmaiah; Sruthi, K; Loni, Rahul; Tanvir, Pasha; Poojar, Sridhar; Lokesh, V (Reports of Radiotherapy and Oncology, 2019)
Background: Accelerated repopulation in HNSCC (head and neck squamous cell cancer) is responsible for poor outcomes; which can be tackled either by hyperfractionation or hypofractionation. Multiple daily fractionations in a setting with more patient load is cumbersome; hence we have tried to escalate the dose to the tumor with SIB by increasing the dose per fraction in the last two weeks of treatment to the tumor; thus, trying to achieve better locoregional control within a shorter period of treatment time. Methods: A total of 20 histologically proven LAHNSCC patients, enrolled alternatively into the control arm (GTV 66Gy, CTVhigh risk 60Gy, and CTVlow risk 54Gy) and the study arm (32Gy to the GTV, CTVhigh risk, CTVlow risk in 16 fractions followed by 30Gy to the GTV, 25Gy to the CTVhigh risk and 20 Gy to CTVlow risk in 10 fractions,), in both arm patients received one fraction per day, five days per week. The radiological response assessment was done using a CT scan at the end of one month after treatment. Toxicity assessment was done weekly during treatment, at the end of treatment, in the first month, and at the end of two months. Results: In this study the patients completed treatment with 26 fractions in about five to six weeks with Grade 3 mucositis in 90% and grade 3 dysphagia in 40% of the patients, which necessitated Ryle’s tube feeding in 30% of the with complete resolution of the mucositis and to grade 1 dysphagia by the end of three months. Grade 1 xerostomia was noted in all the patients with gradual resolution of symptoms. The overall complete response (CR) was achieved in 50% of the patients and the CR with reference to the tumor was seen in 80% and with reference to the node was seen in 50% of the patients, respectively. Conclusions: IMRT with Hypofractionated concomitant simultaneous integrated boost (SIB) was better than standard IMRT with SIB in LAHNSCC, with respect to radiological response, however, at the cost of higher toxicity.